Epic Reversal of the Plot of Guilt from Prokharchin’s Dream to Dmitry Karamazov’s Dream - N. G. Mikhnovets (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article examines the plot of guilt in refraction to the event of a dream from the early story of Fedor Dostoevsky “Mister Prokharchin” to “Brothers Karamazov”. The author of the article proceeds from the idea of the specific features of the writer’s work, characterized by the dynamics of comprehending the main problems for him and the relative stability of their figurative, motivational, plot-plot expression. It is emphasized that the development of the plot was determined by the increased in the 1840–1870s. public interest in the problems of the correlation of the general as a national and individual, the moral transformation of a person, in the peculiarities of folk life and the Russian national character. The constituent parts of the historical and cultural context of Dmitry Karamazov’s dream picture are commented: they determine the thematic structure of this dream, testify to the decisive concretization of the universal human image of “God’s people” (“Mister Prokharchin”) as national. The author of the article comes to the conclusion that in “Brothers Karamazov”, the writer’s reflections on the historical fate and role of the Russian people formed the basis for the epic reversal of the “plot of guilt”: feeling individual guilt, Dmitry Karamazov opens up to a feeling of compassion as a nationwide one.